ANALISIS STRATEGI PEMASARAN BARANG EKSPOR PADA PERUSAHAAN MEBEL UKIR CV. FIKRA INDO EXPORT DALAM MENGHADAPI PERSAINGAN TERHADAP PERUSAHAAN SEJENIS DI KOTA JEPARA - Miftah Arifin; Akhmad Khoirul Anam (Universitas Islam Nahdlatul Ulama Jepara, 2005)
AbstractWhen a condition of economic is less support like now, The Government tries to motivate the export activity whice can appear foreign exchange for country, among of them is none oil and natural gas sector in this case isfurniture industry because the products whic is appeared can compete in abroad market.The aim of this research is toformulate marketing strategi of company toface competition. The analysis is done by identifying the factors whic become Strategic Advantage Profile so can be known the strenghts, the weaknes and external factors of company the result is opportunity and threat can be known.The analysis whic is used is SWOT Analysis (Strengths, Weakness, Opportunities and Threats), whic consists of SAP Analysis (Strategic Advantage Profile) that is to observe the position of company from strength and weaknes side and also ETOP Analysis (Environmental Threat and Opportunity Profile) that is to observe the position of company from the weaknes and the threat.Based on SAP Analysis the company is an a favorable position, it means that prestation of company is satisfying, whereas based on ETOP Analysis the company is an ideal business that is business whic has high success opportunity and low failing risk. From combination of both analysis mentioned on SWOT matrix, the company is on invest position. Keywords: Strengths, Weakness, Opportunities and Threat (SWOT), Strategic Advantage Profile (SAP), Environmental Threat and Opportunity Profile ( ETOP)